PENGARUH FAKTOR PSIKOLOGIS TERHADAP KEPUTUSAN PEMBELIAN ILBAB PASHMINA PADA ANGGOTA HIJABERS COMMUNITY DI LAMONGAN - ROISATUL UMMAH, IFFAH (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
Purchasing decisions are individuals who are directly involved in decisions to make a purchase of a product. Factors that affect the purchasing decision is a factor of culture, social factors, personal factors, psychological factors. This purchasing decision in the psychological factors influence the members of the Hijabers Community in lamongan to take purchasing decisions on hijab pashmina. The variable being put into observation are motivation (X1), perception (X2), learning (X3), attitudes (X4) serve as independent variables while the purchasing decisions defined as dependent variable (Y). This instrumen uses questionnaires as main instrument to get data from 133 respondents. This observation might be conclude that the independent variable altogether are making a partial and simultaneous affection towards the members of the Hijabers Community in lamongan to take purchasing decisions on hijab pashmina. Keywords: psychological factors, purchases of decision